THINKING IN BUSINESS PROCESS MANAGEMENT IS A FEATURE OF DESIGN. - Makhmudov Mukhtorjon Abdumalik o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, Thinking Design is a user-oriented product, or service. Stages of Thinking Design, Empathy as the center of a human-centered design process. Here are some suggestions on how to look or get an appointment for business ideas.